1994
DOI: 10.1128/aem.60.6.1962-1968.1994
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Nisin Z against Listeria monocytogenes Scott A Grown at High and Low Temperatures

Abstract: Nisin Z, a natural nisin variant, was recently isolated from Lactococcus lactis subspecies lactis NIZO 22186. The gene for this lantibiotic, designated nisZ, has been cloned, and its nucleotide sequence was found to be identical to that of the precursor nisin gene with the exception of a single mutation resulting in the substitution of Asn-27 for His-27 in the mature polypeptide (J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
103
1
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(118 citation statements)
references
References 31 publications
12
103
1
2
Order By: Relevance
“…By comparing the rates of pediocin-PA-1-induced ATP depletion and inorganic phosphate e¥ux, Chen and Montville [89] have suggested that the observed depletion of ATP is most likely due to attempts of the cell to regenerate the decreased PMF, rather than a shift in the ATP hydrolysis equilibrium due to the loss of inorganic phosphate. Again, contrasting results have been reported for the lantibiotic nisin Z [91].…”
Section: Bactericidal E¡ectsmentioning
confidence: 71%
“…By comparing the rates of pediocin-PA-1-induced ATP depletion and inorganic phosphate e¥ux, Chen and Montville [89] have suggested that the observed depletion of ATP is most likely due to attempts of the cell to regenerate the decreased PMF, rather than a shift in the ATP hydrolysis equilibrium due to the loss of inorganic phosphate. Again, contrasting results have been reported for the lantibiotic nisin Z [91].…”
Section: Bactericidal E¡ectsmentioning
confidence: 71%
“…Subsequently, it has been shown that nisin kills bacterial cells by interfering with basic energy transduction occurring at the cytoplasmic membrane [166,173,181]. It was found that pores formed in the membrane by the nisin molecules allowed the di¡usion of small compounds, since no transport system for ATP has been reported [173,186]. The increase in membrane permeability results in the collapse of the PMF; in the case of nisin, both the vpH and the vi are completely dissipated leading to a rapid cessation of all biosynthetic processes [173,175,187,188].…”
Section: Biological Activity Of Nisinmentioning
confidence: 99%
“…Nisin interferes with the cytoplasmic membrane of sensitive species, leading to pore formation, and dissipates the proton motive force. This allows e¥ux of low-molecularmass solutes such as amino acids and K [8]. The e¤cacy of nisin as an antibacterial agent would be compromised by the emergence of nisin-resistant bacteria in a food-processing situation.…”
Section: Introductionmentioning
confidence: 99%